2017
DOI: 10.1111/grs.12138
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cadmium tolerance of 21 cultivars from Italian ryegrass (Lolium multiflorum Lam) during germination

Abstract: The cadmium (Cd) tolerance of 21 Italian ryegrass (Lolium multiflorum Lam.) were investigated in this study by evaluating the process of seed germination on exposure to excess Cd. Excess Cd resulted in the significant growth inhibition, particularly of root growth. The relation between Cd concentrations and inhibition rate of root or shoot elongation can be well described by a logarithmic equation. The maximum values of IC50 (Cd concentration when the root or shoot elongation decreased to 50% compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In addition, both species are salt tolerant and have potential in improving degraded soil. Previous studies have reported seed germination responses of this species to temperatures ( Shen et al, 2008 ), cadmium stress ( Fang et al, 2017 ) with either annual or perennial ryegrass. However, no information is available on germination responses of annual and perennial ryegrass seeds to the interactive effects of temperature and salt-alkali stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both species are salt tolerant and have potential in improving degraded soil. Previous studies have reported seed germination responses of this species to temperatures ( Shen et al, 2008 ), cadmium stress ( Fang et al, 2017 ) with either annual or perennial ryegrass. However, no information is available on germination responses of annual and perennial ryegrass seeds to the interactive effects of temperature and salt-alkali stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivar dependent Cd sensitivity in tested wheat cultivars under Cd exposure Cultivar-dependent differential Cd tolerance has been reported in various plants such as maize (Akhtar et al, 2017), Amaranthus gangeticus (He et al, 2018), Italian ryegrass (Fang et al, 2017) and rice (Hou et al, 2018). In current study, different Cd tolerance and tissue vulnerability to Cd toxicity in three tested cultivars were unravelled.…”
Section: Discussionmentioning
confidence: 51%
“…Cultivar-dependent differential Cd tolerance has been reported in various plants such as maize (Akhtar et al 2017), Amaranthus gangeticus (He et al 2018), Italian ryegrass (Fang et al 2017), and rice (Hou et al 2018). In current study, different Cd tolerance and tissues vulnerable to Cd toxicity in three tested cultivars were unraveled.…”
Section: Cultivar Dependent CD Sensitivity In Tested Wheat Cultivars mentioning
confidence: 63%